Housing Financing Strategy through FLPP (Housing Financing Liquidity Facility) in Indonesia - Akbar, Faisal; Ramadhan, Muhammad; Sugianto, Sugianto (Universitas Pendidikan Ganesha, 2025)
This study examines the implementation of the Housing Financing Liquidity Facility Program (FLPP) as a government effort to enhance access to decent and affordable housing for low-income communities (MBR). Using a qualitative approach, the study collected data through in-depth interviews with stakeholders and a comprehensive literature review, allowing for an in-depth understanding of practical challenges and opportunities. The findings indicate that while FLPP effectively expands homeownership access for MBR, it faces challenges such as complex administrative procedures, documentation difficulties for informal workers, low financial literacy, limited availability of suitable housing, and suboptimal location choices. A SWOT analysis highlights policy support and institutional collaboration as key strengths, while rising material costs and restricted land availability are significant threats. Based on these findings, the study recommends strategies including digitization of services, targeted financial education, local needs-based housing development, diversification of financing schemes, and ongoing data-driven evaluation. By linking qualitative insights directly to these recommendations, the study demonstrates how FLPP can be optimized and scaled to support broader inclusive and sustainable development objectives, reinforcing the role of local governments and the private sector in enhancing housing welfare for MBR.